Erythrasma - A red herring in the ongoing epidemic of tinea - V Ramesh; Shanta Passi (Wolters Kluwer Medknow Publications, 2022)
We describe the presentation of five adults with erythrasma, misdiagnosed as tinea and prescribed antifungal treatment which resulted in incomplete clearance. The lesions were restricted to axillary and/or inguinal folds. They were dry, brown macules with fine scaling. Except for one with moderate pruritus, they were asymptomatic. No fungal elements could be demonstrated in any of the patients in 10% KOH preparation. Gram stain revealed short gram-positive rods in varying proportions. All the patients showed a pink fluorescence on Wood's lamp examination. After treatment with topical clindamycin singly or in combination with oral azithromycin, there was complete clearance of the lesions leaving normal-appearing skin in three and residual hyperpigmentation in one. The overdiagnosis of tinea in the ongoing epidemic of dermatophytosis is a potential concern. Wood's lamp examination is very useful to confirm or exclude erythrasma.